QUALITATIVE IDENTIFICATION OF BORAX (H3BO3) IN MEATBALLS USING HIBISCUS FLOWER (HIBISCUS ROSA-SINENSIS L.) - Farica Rasendriya; Revi Sukmawati; Salma Nuraini Safitri; Rizki Nor Amelia (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
Meatballs are one of the favorite processed foods. They are round and made from livestock meat with starch or cereals. The texture and chewiness of meatballs should be determined by the meat used as the main ingredient in the production process. Still, borax is usually added to reduce production costs, which, if consumed continuously, can interfere with health. Therefore, this study aims to identify the presence of borax in meatballs in Sekaran Village, Semarang City, with the natural indicator of hibiscus flowers. Hibiscus flowers were chosen because they contain anthocyanin extract that can be used as a qualitative indicator of the presence of borax compounds in a food sample. The test results showed that all five meatball samples were positive, as evidenced by the formation of a purple ring with a white base on the indicator paper. This indicates that the public still needs to be vigilant when consuming food, and related agencies still need to intervene to conduct periodic checks and withdraw various food products, especially those containing borax compounds.